New records of deep-sea ascidians (Tunicata, Ascidiacea) from the New Caledonia region - Monniot, Francoise (Zootaxa, 2021)
The deep marine bottoms around New Caledonia have been explored for forty years. The Kanacono (2016) and Kanadeep (2019) campaigns organized jointly by the Muséum national d’Histoire naturelle (MNHN) and the Institut de Recherche pour le Développement (IRD) are the complement of this investigation. They are a part of the program “La Planète Revisitée” in New Caledonia. Among the deep sea benthos twenty two ascidian species were collected and three represent new species showing the characteristic adaptations to an abyssal life. The high diversity of the tropical deep sea benthos is enhanced by these new results. No relations are found between littoral ascidians and forms living in the bathyal or abyssal areas.